Indians, twins and scleroderma: genetic and genomic studies - Arnett, Frank (Henry Stewart Talks, 2007)
The genetics of scleroderma, What is the evidence that it is genetic?, Familial aggregation and twin studies, The use of large case-control studies to identify the genes, The emerging genetic heterogeneity of the disease, The use of genomic approaches to discover the molecular pathways contributing to this disease, Using microarrays to better understand pathogenesis and to define prognosis
Archived at 2016/06/30